2012
DOI: 10.1370/afm.1381
|View full text |Cite
|
Sign up to set email alerts
|

Program to Improve Colorectal Cancer Screening in a Low-Income, Racially Diverse Population: A Randomized Controlled Trial

Abstract: PURPOSE More effective strategies are needed to improve rates of colorectal cancer screening, particularly among the poor, racial and ethnic minorities, and individuals with limited English profi ciency. We examined whether the direct mailing of fecal occult blood testing (FOBT) kits to patients overdue for such screening is an effective way to improve screening in this population. METHODSAll adults aged 50 to 80 years who did not have documentation of being up to date with colorectal cancer screening as of De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…23,24,26,27 Two groups have studied effects of outreach with patient navigation, including mailed invitation, telephone follow-up, and patient navigation among underserved primary care patients, reporting increases in screening of 13% to15.5% above usual care. 26,27 Lasser et al 26 offered choice of colonoscopy or gFOBT, while Percac-Lima et al 27 offered colonoscopy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24,26,27 Two groups have studied effects of outreach with patient navigation, including mailed invitation, telephone follow-up, and patient navigation among underserved primary care patients, reporting increases in screening of 13% to15.5% above usual care. 26,27 Lasser et al 26 offered choice of colonoscopy or gFOBT, while Percac-Lima et al 27 offered colonoscopy alone.…”
Section: Discussionmentioning
confidence: 99%
“…13,1822 Mailed outreach efforts with stool testing have been successful in underserved populations, but these efforts used the more cumbersome guaiac fecal occult blood test (gFOBT), which requires multiple stool samples and strict diet restrictions. 2325 Mailed outreach with colonoscopy invitations has also been tested among the underserved, and shown promise. 26,27 Whether mailed outreach with the more convenient FIT, which does not require diet restriction and can be performed with 1 sample, is effective in for underserved populations, and how FIT outreach compares with colonoscopy outreach are unknown and merit further study.…”
mentioning
confidence: 99%
“…These included, for example, those based on telephone outreach and the mailing of FOBT kits directly to at-risk individuals [45], and health-fair style screening for the uninsured [46]. …”
Section: Iraqi Women In Americamentioning
confidence: 99%
“…Previous evaluations of clinic-based programs to improve rates of CRC screening have shown that direct mailing of fecal occult blood tests (gFOBT) or fecal immunochemical tests (FIT) consistently led to 6–30% increases in CRC screening, regardless of clinical setting [1115;15;16]. Some studies have shown that use of health educators and screening information tailored to specific cultural and language needs can be effective in raising CRC screening rates [11;13;1719].…”
Section: Introductionmentioning
confidence: 99%